2002
DOI: 10.1038/sj.thj.6200175
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in patients with advanced multiple myeloma: a study of 83 patients–report of the intergroupe francophone du myélome (IFM)

Abstract: Thalidomide is an effective treatment for patients with advanced myeloma, in particular, who have no poor-risk features. The poor results achieved by the other patients emphasize the need for prospective protocols using thalidomide in combination, especially with dexamethasone. In addition, further studies are needed to determine the optimal thalidomide dose and duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 0 publications
4
55
2
1
Order By: Relevance
“…Since PCLI and cytogenetics are usually not available in the standard practice setting outside of specialised centres, b2M and CRP have an independent prognostic importance for survival. The results of our study confirm the results obtained by Singhal et al (1999) and Yakoub-Agha et al (2002) that the albumin serum level is a useful parameter, determining the response to THAL treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Since PCLI and cytogenetics are usually not available in the standard practice setting outside of specialised centres, b2M and CRP have an independent prognostic importance for survival. The results of our study confirm the results obtained by Singhal et al (1999) and Yakoub-Agha et al (2002) that the albumin serum level is a useful parameter, determining the response to THAL treatment.…”
Section: Discussionsupporting
confidence: 91%
“…19 Response rates of about 30% reported by Singhal et al 8 were confirmed by others groups. 9,[20][21][22][23] Addition of dexamethasone to thalidomide in patients who failed to benefit from prior therapy, including both thalidomide and dexamethasone given as single agents, further increased responses, up to an overall response rate of 50-55%. 10,11 These data suggested a synergy between thalidomide and dexamethasone and prompted several groups to explore this combination also in patients with previously untreated MM.…”
Section: Discussionmentioning
confidence: 99%
“…Number of days to ANC4500/ml 11 (9-16) PLTC420 000/ml 14 (10-22) PLTC450 000/ml 17 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) PLT transfusions (no.) 3 (0-16) RBC transfusions (no.)…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide monotherapy has recently been shown to be active in relapsed or refractory multiple myeloma with response rates (> 25% serum paraprotein reduction) ranging between 32% and 66% Juliusson et al, 2000;Rajkumar et al, 2000;Hus et al, 2001;Yakoub-Agha et al, 2002). Responses were more frequent in patients with a low plasma cell labelling index and normal cytogenetics , whereas a dose-response effect was demonstrated, especially for highrisk patients (Barlogie et al, 2000).…”
mentioning
confidence: 99%